2022
DOI: 10.21037/jtd-22-937
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C is a potential predictor of short-term mortality and acute kidney injury in acute aortic dissection patients: a retrospective cohort study

Abstract: Background: Serum cystatin C concentration is associated with cardiovascular disease. However, the relationship between cystatin C and acute aortic dissection (AAD) remains unclear. In the current study, we aim to evaluate the predictive value of cystatin C in the occurrence of acute kidney injury (AKI) and the prognosis of AAD patients. Methods:The patients with AAD admitted to our hospital from November 2019 through January 2022 were consecutively included in the retrospective cohort study. A complete blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…In this study, the prevalence of postoperative AKI in aortic dissection patients was found to be 20.29%, which is lower than in previous studies 22 , 23 , 24 and may be due to the lower mean age of the participants in this research. Meanwhile, the results of the present study confirm and extend previous findings.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, the prevalence of postoperative AKI in aortic dissection patients was found to be 20.29%, which is lower than in previous studies 22 , 23 , 24 and may be due to the lower mean age of the participants in this research. Meanwhile, the results of the present study confirm and extend previous findings.…”
Section: Discussioncontrasting
confidence: 82%
“…Serum cystatin C is eliminated solely via glomerular filtration and can be easily measured [ 34 ]. Compared with urea and creatinine, the serum cystatin C concentration increases earlier when the kidney is injured [ 35 ], and it is a useful predictor of short-term mortality and AKI in acute aortic dissection patients [ 36 ]. INR is a standardized measure of the extrinsic coagulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several novel biomarkers for AKI have been evaluated in aortic surgery. The most studied biomarkers, derived from urine or plasma samples, are related to cell cycle arrest, such as NGAL, liver-type fatty acid-binding protein (L-FABP), IGFBP-7, TIMP-2, and cystatin C [ 7 , 8 , 9 , 10 , 11 , 29 , 30 , 31 , 32 ]. A few studies have evaluated the predictive ability of blood immune-inflammatory biomarkers such as plasma secretory leukocyte peptidase inhibitor (SLPI), pentraxin 3 (PTX3), IL1-RA, MCP-1, suppressor of tumorigenicity 2 (ST-2), IL-6, and IL-10 [ 19 , 20 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%